The agronomic variability of a collection of sainfoin acceáions - Delgado, I.=700 1 Salvia, J.; Buil, I.; Andres, C.
(Es, En)
Ilus., 16 ref.
Keywords: ONOBRYCHIS VICIIFOLIA; CRECIMIENTO; ECOTIPOS; FLORACION; REBROTE; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH